2015
DOI: 10.3748/wjg.v21.i23.7197
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin inhibits human gastric carcinoma cell proliferation through up-regulation of microRNA-124 and suppression of PI3K/Akt and STAT3 signaling

Abstract: In summary, the in vitro data suggest that paeoniflorin is a potential novel therapeutic agent against gastric carcinoma, which inhibits cell viability and induces apoptosis through the up-regulation of miR-124 and suppression of PI3K/Akt and STAT3 signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 35 publications
4
56
0
Order By: Relevance
“…Paeoniflorin inhibits activity of gastric cancer cell MGC-803 and induces apoptosis, through up-regulating miR-124 and inhibiting pathways of phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) and signal-activated transcription factors 3 (STAT3) [33] 2.5, 5, 10 lg/ml Gastric cancer fibroblast GCAFs Inhibit metastasis and invasion of GCAFs through targeted inhibition of pathway IL-6-STAT3-MMP [33] Breast cancer 12.5-50 lmol/l Human breast cancer cell lines MDA-MB-231 and MCF-7 PF inhibits expression of HIF-1a through regulating pathway PI3K/Akt, protects against breast cancer cell hypoxia-induced epithelial-to-mesenchymal transition (EMT) [36] Inhibit proliferation and invasion of breast cancer cell through inhibiting pathway Notch-1 [37] 0, 7.5, 15, 30 lmol/l Breast cancer cell line MCF-7 Inhibit proliferation and invasion of breast cancer cell through inhibiting pathway Notch-1 [38] Lung cancer 40 mg/kg per day Lewis lung carcinomabearing mice model Inhibit tumour growth of Lewi lung carcinoma-bearing mice, and inhibit lung metastasis of Lewi lung carcinoma-bearing mice [40] 1, 3, 10, 30, 100 lmol/l; 20, 40 mg/kg…”
Section: Human Gastric Cancer Cell Line Sgc7901vincristine Vcrmentioning
confidence: 99%
“…Paeoniflorin inhibits activity of gastric cancer cell MGC-803 and induces apoptosis, through up-regulating miR-124 and inhibiting pathways of phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) and signal-activated transcription factors 3 (STAT3) [33] 2.5, 5, 10 lg/ml Gastric cancer fibroblast GCAFs Inhibit metastasis and invasion of GCAFs through targeted inhibition of pathway IL-6-STAT3-MMP [33] Breast cancer 12.5-50 lmol/l Human breast cancer cell lines MDA-MB-231 and MCF-7 PF inhibits expression of HIF-1a through regulating pathway PI3K/Akt, protects against breast cancer cell hypoxia-induced epithelial-to-mesenchymal transition (EMT) [36] Inhibit proliferation and invasion of breast cancer cell through inhibiting pathway Notch-1 [37] 0, 7.5, 15, 30 lmol/l Breast cancer cell line MCF-7 Inhibit proliferation and invasion of breast cancer cell through inhibiting pathway Notch-1 [38] Lung cancer 40 mg/kg per day Lewis lung carcinomabearing mice model Inhibit tumour growth of Lewi lung carcinoma-bearing mice, and inhibit lung metastasis of Lewi lung carcinoma-bearing mice [40] 1, 3, 10, 30, 100 lmol/l; 20, 40 mg/kg…”
Section: Human Gastric Cancer Cell Line Sgc7901vincristine Vcrmentioning
confidence: 99%
“…Treatment with bevacizumab mAbs for 24 h prior to FP chemotherapy significantly increased the apoptotic ratio of cells in the S phase. Other studies showed that [16][17][18][19][20] cell cycle arrest in S phase can reduce the number of cells that undergo mitosis, interfere with DNA synthesis, and enhance the cytotoxicity of 5-FU, thereby increasing tumor cell apoptosis and inhibiting tumor cell growth and proliferation.…”
Section: Discussionmentioning
confidence: 97%
“…It also inhibited inflammatory pain via modulation of N‐methyl‐D‐aspartate in the brain cortex and reduced related cytokines, such as tumor necrosis factor‐α (TNF‐α), interleukin (IL)‐1β, IL‐6, IL‐10, IL‐12, and IL‐17 (Dai et al, ; Sun et al, ; Xu et al, ). Paeoniflorin upregulated apoptosis of MGC‐803 human gastric carcinoma cells and HT29 human colorectal cancer cells (Chen, Lee, et al, ; Parker et al, ; Zheng et al, ). It inhibited proliferation, invasion, and metastasis of MCF‐7/MDA‐MB‐231 human breast cancer cells and human A549 lung cancer cells (Parker et al, ; Zhang, Yuan, Cui, Xiao, & Jiang, ; Zhou, Wang, Song, & Hu, ).…”
Section: Discussionmentioning
confidence: 99%